Can AnyExperts' dynamic expert allocation maintain consistent accuracy improvements over dense baselines when - Assignee Research (Assignee Research, 2026)
Despite their remarkable achievement, gigantic transformers encounter significant drawbacks, including exorbitant computational and memory footprints during training, as well as severe collapse evidenced by a high degree of parameter redundancy. Sparsely-activated Mixture-of-Experts (SMoEs) have shown promise to mitigate the issue of training efficiency, yet they are prone to (1) redundant experts due to representational collapse; and (2) poor expert scalability for inference and downstream fine
Machine-generated literature synthesis.